Identification of problems in teaching Pilipino in public secondary schools in the Division of Isabela, 1962-1963 - Bacud, Virginia S. 1918- (s.n.], 1963)
This study investigates the problems of teaching Pilipino in the public secondary schools of Isabela according to sources such as: students, instructional materials, methods and techniques, teachers and administrators, and suggestions on how to minimize these identified problems from the point of view of the teachers themselves.